DONALD: A 2.5 T wide sample space permanent magnet. (April 2018) - Potticary, Jason; Avery, Michael P.; Mills, Doug; Hall, Simon R.
Graphical abstract: Abstract: The permanent magnet apparatus described herein is based upon the C-shaped permanent magnet. It is designed to maximise field strength while increasing the pole gap to 5 mm, providing a sample volume large enough for wide applicability. The production of this equipment aims to provide a homogeneous, high field (∼2.5 T) magnetic sample environment with a volume large enough to accommodate solution crystallisation experiments in sample chambers such as NMR tubes and cuvettes whilst simultaneously allowing direct observation of the sample from a wide angle. Although the resulting rig is not lightweight at 26.5 kg it is eminently more portable than an equivalent electromagnet system (of the order of 625 kg), and provides a max field strength of 2.468 T with relatively low stray field.